The Effect of Bengkulu Cultural Portraits on Students’ Descriptive Writing Ability: A Quasi-Experimental Study at MTs Ja-Alhaq Bengkulu - Fitri, Nurul; Suradi, Ahmad; Putri Juni Astuti, Dina (Yayasan Darussalam Bengkulu, 2024)
Writing is a fundamental language skill that plays a critical role in shaping students’ ability to communicate ideas effectively, yet many junior high school students struggle with descriptive writing due to limited vocabulary, lack of imagination, and monotonous teaching methods. This study aimed to examine the effect of integrating Bengkulu cultural portraits as visual media on the descriptive writing ability of seventh-grade students at MTs Ja-Alhaq Bengkulu. A quasi-experimental design was employed with two groups: the experimental group (n = 25) was taught using Bengkulu cultural portraits, while the control group (n = 25) received instruction through conventional methods. Data were collected through pretests and posttests and analyzed using normality, homogeneity, paired-sample t-tests, independent-sample t-tests, and N-Gain scores with the aid of SPSS 25.0. The results demonstrated that the experimental group achieved a higher posttest mean score (M = 76.84) compared to the control group (M = 60.68), with an N-Gain of 0.4656 (47%), indicating a moderate level of effectiveness. Statistical analysis confirmed a significant difference (p = 0.001 < 0.05), showing that the use of Bengkulu cultural portraits substantially improved students’ descriptive writing performance. These findings suggest that integrating local cultural media not only enhances students’ cognitive outcomes in writing but also fosters engagement and cultural awareness. The novelty of this research lies in its focus on Bengkulu cultural artifacts as a contextualized teaching medium, which has been underexplored in previous studies. The implications highlight the importance for educators and policymakers to incorporate local cultural resources into language learning curricula as a strategy to improve academic achievement while simultaneously preserving cultural heritage.